Analysis on the effect of stimulator parameters in electrical stimulation procedure on the human bicep muscle - Azman, Amelia Wong; Naeem, Jannatul; Mohd Mustafah, Yasir; Mohamad, Saforazuridi; Khan, Sheroz; Alam, A. H. M. Zahirul; Habaebi, Mohamed Hadi (Penerbit UTM Press, 2016)
While electrical stimulation has proven to produce positive outcome among patients, electrical stimulation in post stroke rehabilitation faced one main limitation – muscle fatigue. Muscle fatigue limits the training time, hence, affecting the recovery process. This work analyzes the occurrence of muscle fatigue with respect to the different stimulator parameters; amplitude, pulse shape and frequency. The detection of muscle fatigue will be monitored as force where the force sensitive resistor (FSR) sensors are used to detect the variations of the force exerted by the muscle. In this work, it is assumed that the fatigue in muscle will happen when the force recorded reduces to 60% from its initial force over the stimulation period. The experiment results proof that the stimulator parameters, amplitude, pulse shape and frequency, have different effect to the upper limb muscle with respect to muscle fatigue. The results also show that the exponential waveform can be considered in future rehabilitation program since the onset of muscle fatigue is delayed later in the experiment when compared to the other signals. This allows extended training duration among stroke patients to benefit from the recovery window time frame especially for patients who are still in their early recovering stage.